Analisis Kepuasan Konsumen Terhadap Oleh Oleh Khas di Sentra Toko Oleh Oleh Anggut Atas Kota Bengkulu - Mutmainnah, Elni; Firmansyah, Trio Epan; Mulyadi, Maheran; Yawahar, Jon (Jurnal MeA (Media Agribisnis), 2024)
The development of various industries, especially small and medium enterprises, provide business opportunities for the community. However, the emergence of many new businesses has made competition fiercer. Therefore, a good strategy is needed to compete in the market. This research aims to 1) determine the level of consumer satisfaction towards typical souvenirs of Bengkulu, 2) identify the attributes that consumers consider when buying typical souvenirs at the Anggut Atas souvenir center in Bengkulu city. The method used in this research is a survey method involving 100 respondents who purchased souvenirs at the Anggut Atas souvenirÂ  center in Bengkulu city by using accidental sampling. The analysis used a combination of Costumer Satisfaction Index (CSI) And Importance Performance Analisis (IPA). The results showed that the level of consumer satisfaction with souvenir products was 77.87, which falls into the category of consumers feeling satisfied whit the service provided. The IPA testing results identified attributes falling into Quadrant I (Priority) for development, including affordability, discounts, security, visitor parking, employee tidiness, store decoration, payment process, and adequate transportation.